Isolation of Bacteriophages Specific for Lactobacillus casei ATCC 393 Strain 03 and Streptococcus mutans ATCC 35668 from Human Saliva - Lim, Jia Wen (2015)
Streptococcus mutans and Lactobacillus casei are common microflora of the human oral cavity. Bacteriophages are important to ensure controlled microbial population in the oral cavity. Hence, isolation of the bacteriophages specific for S. mutans ATCC 35668 and L. casei ATCC 393 strain 03 from human saliva samples were done using the Double Agar Overlay Plaque Assay. Ten individuals aged 18-25 years old from INTI International University willingly provided the saliva samples for the isolation of bacteriophages of the mentioned bacteria. The saliva from all the individuals were collected at week 2, week 6 and week 9 of August 2014 session to study the effect of different stress level, diet, sleeping hours and oral hygiene practices to the presence of the bacteriophages. However, no bacteriophage specific for S. mutans ATCC 35668 and L. casei ATCC 393 strain 03 were isolated from the study.